Misfits of avalon (2014), volume 3 ebook The future in the wind. - McDonald, Kel (Misfits of Avalon (2014), 2018)
Smart-mouthed teens Elsie, Kimber, Morgan, and Rae have enough to handle with magical rings, talking dogs, and faeries, but when they discover that the knight they've been battling for Excalibur is a familiar face with a mission of his own, they must get to the bottom of the real intentions behind the quest they were given. Misfits of Avalon reaches its conclusion in this final volume!